Some New Information on the Ethnic and Cultural Processes in the Neolithic Upper Volga Region - Yuri B. Tsetlin (Археология евразийских степей)
This article was prepared in connection with Aleksander Alekseyevich Vybornov’s jubilee and is dedicated to the history of the Upper Volga region population during the Neolithic Age. Based on the study of pottery decoration traditions, the author reconstructs the history of the Neolithic population six groups (Volga-Oka culture, Upper Volga culture, dotted-and-combed ceramics culture, Volosovo culture and the groups with rare-dotted and rare-dotted thin-walled pottery) and their contacts with each other. A cultural core and cultural periphery are distinguished within each of the population groups. In the final part of the paper, the author presents his understanding of the ethnic and cultural process development of the population in the Upper Volga region and proposes a new content of the concept "archaeological culture". The presented theses are based on many years laborious study of the Neolithic complexes of the Upper Volga region.